The Meaning of Traditional Titles in the Traditional Marriage Ceremony of the South Sumatra Komering Community - Arifai, Ahmad; Huda, Noor; Anwar, M. Saidun (EDUCATE : Journal of Education and Culture, 2023)
The tradition of giving customary titles is interesting to study because of some of the problems in it. Among other things, why was the awarding of the Komering wedding ceremony given to all people? What is the background for giving customary titles? How is the community wedding procession Komering? Some of the problems above are unique and different from the customs of other ethnic groups in Indonesia. This study took the location of Tanjung Lubuk Ogan Komering Ilir Subdistrict, South Sumatra. By using the theory of symbols put forward by Victor Turner with an ethical approach, namely categorization comes from researchers who refer to previous concepts, and emics, namely categorization of phenomena according to local residents (cultural owners). Data collection in this study was carried out with three techniques namely observation, in-depth interviews and secondary data tracing. In this study, researchers used qualitative analysis. Because this research is included in cultural research. The result of this research is that the awarding of customary titles is an ancient Malay cultural heritage, especially the Hindu cultural heritage of the Srivijaya period, which is still preserved today. This tradition is carried out when young women in the Komering community reach adulthood which are marked by a marriage. At that time it was a transition from adolescence to adulthood, so it should be given an honor in the form of a traditional title alias title.